Temperature Impact on The ION/IOFF Ratio of Gate All Around Nanowire TFET - Agha, Firas Natheer Abdul-kadir; Hashim, Yasir; Shakib, Mohammed Nazmus (IEEE Xplore, 2020)
This research paper presents the effect of working temperature on the ION, IOFF and ION/IOFF ratio of gate all around nanowire TFET. The (Silvaco) simulation tool has been used to investigate the temperature characteristics of a transistor. The working temperature range of this study is from -50 to 150 step-up 25 oC. The final results indicate that the negative effects of increasing working temperature of gate all around nanowire TFET due to decreasing of the ION/IOFF ratio. Hence, the results for ION/IOFF ratio vs. working temperature characteristics may lead to the use of TFET in electronic circuits with lowest possible working temperature to obtain higher ION/IOFF ratio.